EVALUATION OF ANTI-BULLYING PROGRAMS IN PRIMARY SCHOOLS: STRATEGIES AND THEIR IMPACT ON SAFE LEARNING ENVIRONMENTS - Mahmudah Mahmudah; Tamjidnor Tamjidnor (Adisam Publisher, 2025)
This literature review aims to examine the effectiveness of an anti-bullying program in creating a safe learning environment in an elementary school setting. The study was motivated by the increasing incidence of bullying in schools which has a negative impact on students' mental health and academic performance. Based on these observations, this study aims to identify evidence-based strategies that can tackle the problem of bullying and promote a positive and supportive learning environment for all students. The research method used a literature review. The results showed that anti-bullying programs that involve all school components, including students, teachers and parents, are the most effective in creating a safe learning environment. Interventions that focused on empathy education, social skills training for students, and training for teachers in recognizing and responding to bullying incidents proved significant in reducing the incidence of bullying. In addition, parental involvement in bullying education and prevention programs had a positive impact in strengthening school efforts. Last but not least, the findings show that restorative approaches that emphasize mediation and conflict resolution are effective in improving relationships between perpetrators and victims, as well as building a more inclusive and supportive school culture.